2017
DOI: 10.1248/cpb.c17-00300
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of <i>Corydalis ternata</i> Extract and Its Phytochemical Quantitative Analysis

Abstract: The tubers of Corydalis ternata have been used to treat cardiovascular diseases such as hypertension and cardiac arrhythmia. Its active components have anticholinesterase, antiamnesic, and anti-inflammatory activities, and analgesic effects. In the present study, we performed quantitative analyses of the two components of C. ternata, coptisine and berberine, using HPLC. A 70% ethanol extract of C. ternata was prepared and the two components were separated using a C-18 analytical column on a gradient solvent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In these methods, UV detection was sensitive enough for the analysis of BAs. Besides UV detectors, DAD detectors have also been used in many analytical methods, especially in the analysis of multi-component samples [20][21][22][23][24]. Mahoniae Caulis was selected as an example to develop and validate the method for the simultaneous determination of four alkaloids (berberine, columbamine, jatrorrhizine, and palmatine) using HPLC-DAD at 345 nm with an Agilent Zorbax SB-AQ C18 column [20].…”
Section: Hplcmentioning
confidence: 99%
“…In these methods, UV detection was sensitive enough for the analysis of BAs. Besides UV detectors, DAD detectors have also been used in many analytical methods, especially in the analysis of multi-component samples [20][21][22][23][24]. Mahoniae Caulis was selected as an example to develop and validate the method for the simultaneous determination of four alkaloids (berberine, columbamine, jatrorrhizine, and palmatine) using HPLC-DAD at 345 nm with an Agilent Zorbax SB-AQ C18 column [20].…”
Section: Hplcmentioning
confidence: 99%
“…More specifically, the TCMs corresponding to mGluR І and mGluR ІІІ mostly possess bitter flavor and pungent flavor; the mGluR ІІ is relevant to bitter flavor. Many TCMs have been proven to be effective Chinese medicines to treat neurological diseases, including Corrydalis yanhusuo (Yan Hu Suo) [ 36 ], Psoralea corylifolia Linn (Bu Gu Zhi) [ 37 ], and Radix Paeoniae Alba (Bai Shao) [ 38 ]. Specifically, Corrydalis yanhusuo [ 36 ] and Psoralea corylifolia Linn [ 37 ] play neuroprotective effects through treatment of dementia and oxidative stress, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many TCMs have been proven to be effective Chinese medicines to treat neurological diseases, including Corrydalis yanhusuo (Yan Hu Suo) [ 36 ], Psoralea corylifolia Linn (Bu Gu Zhi) [ 37 ], and Radix Paeoniae Alba (Bai Shao) [ 38 ]. Specifically, Corrydalis yanhusuo [ 36 ] and Psoralea corylifolia Linn [ 37 ] play neuroprotective effects through treatment of dementia and oxidative stress, respectively. In addition, Radix Paeoniae Alba [ 38 ] could treat Parkinson’s disease by reducing the MPTP-induced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Validating reference genes under certain environmental treatments and in different species is necessary [44,45]. Though the extract of C. yanhusuo has been used in promoting blood circulation, inhibiting cancer cell proliferation, and as an analgesic agent, no reliable reference genes have been selected in this species [2,16,46]. In order to determine the most reliable reference gene, 12 candidate genes were chosen based on the TAIR dataset and previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Corydalis yanhusuo is a plant from the Papaveraceae family and is widely used to treat drug addiction and as analgesics in China [1]. Abundant pharmacological effects on humans have been identified in the extracts of C. yanhusuo (tuber), such as pain relief, anti-tumor effects, and promotion of blood circulation [2,3]. Benzylisoquinoline alkaloids are the main biological components produced by C. yanhusuo, and previous studies have found that dehydrocorybulbine, which is found in the extract of C. yanhusuo, is a kind of alkaloid that can exhibit antagonistic activity by acting on dopamine receptors [4,5].…”
Section: Introductionmentioning
confidence: 99%